Gender messages in contemporary Malay songs - Collin, Jerome (Issues in Language Studies, 2013)
Gender has been an important area of research in the field of popular music studies. Numerous scholars have found that contemporary popular music functions as a locus of diverse constructions and expressions of gender. While most studies focus on content analyses of popular music, there is still a need for more research on audience’s perception of popular music’s messages. This study examined adult Malay listeners’ perceptions of gender messages in contemporary Malay songs. A total of 16 contemporary Malay songs were analysed using Fairclough’s (1992) method of text analysis. The content of the songs that conveyed messages about gender were the basis for analysis. The results showed that the messages revolve mainly around socially constructed gender roles and expectations in romantic relationships. Gender stereotypes are also used in the songs to reinforce men’s and women’s roles in romantic relationships. The results also showed that, while listeners acknowledge the songs’ messages about gender, their own perceptions of gender and what it means to be a gendered being in today’s world are neither represented nor discussed fully in the songs analysed. It is hoped the findings from this, particularly the mismatch between projected and perceived notions of gender, contribute to the field of popular Malay music studies in particular, and popular music studies in general where gender messages in popular songs and their influence on listeners’ perceptions of their own gender is concerned.